2018
DOI: 10.15406/bbij.2018.07.00206
|View full text |Cite
|
Sign up to set email alerts
|

Perception towards research among undergraduate physical therapy students

Abstract: Objective: To know the perception of students regarding Research among undergraduate physical therapy students. Material and methods: This was an observational cross sectional study with nonprobability convenience sampling technique. The data was collected from different physical therapy institutes, Isra Institute of Rehabilitation sciences Karachi and Isra University Hyderabad. The duration of the study was July to December 2014. Inclusion criteria were Final year undergraduate Physical Therapy Students, eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The presented study showed that PT undergraduate students in KSA have a moderately positive attitude towards research (50.7 ± 10.23). A previous study reported that 84% of respondents strongly agreed that research at undergraduate level is necessary for positive growth of the profession [20]. Similarly, medical students displayed moderate attitude towards research in different countries, including KSA [12], Malaysia [10], Pakistan [21,22], and Croatia [23].…”
Section: Discussionmentioning
confidence: 99%
“…The presented study showed that PT undergraduate students in KSA have a moderately positive attitude towards research (50.7 ± 10.23). A previous study reported that 84% of respondents strongly agreed that research at undergraduate level is necessary for positive growth of the profession [20]. Similarly, medical students displayed moderate attitude towards research in different countries, including KSA [12], Malaysia [10], Pakistan [21,22], and Croatia [23].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, they should provide them with the necessary consultation and support (Henricson et al, 2018). Students underline that the biggest impediment to undertaking research is a lack of mentoring and support (Arif et al, 2018;El Achi, 2020). One of the main functions of university education is to provide students with research experience and skills, as well as a positive attitude toward them.…”
Section: Discussionmentioning
confidence: 99%
“…By exploring students' motivations and understanding of research, as well as their familiarity with research procedures at the undergraduate level, this study seeks to illuminate the perception-related challenges faced by students (35). Addressing these challenges is of paramount importance for fostering a positive research culture among future healthcare professionals (36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%